Femoral hernias occur in both genders - Elize W. Lockhorst; Jasper van der Slegt; Eelco J. Veen; Dagmar I. Vos (Elsevier, 2020)
Femoral hernias are uncommon in children, due to the unfamiliarity it is an often misdiagnosed condition. In this article, we present a 6-year old male patient and a 14-year old female patient. Initially the patients were diagnosed with a inguinal hernia and a hydrocele of the canal of Nuck, respectively. In the first case the patient returned after the first surgery with a recurring bulging, during the surgical exploration of the second surgery a femoral hernia was found. In the second case a femoral hernia was observed during surgery instead of a hydrocele of the canal of Nuck. With the aim of preventing misdiagnosis, clinicians must be aware of femoral herniation in children, especially when clinical presentation is not typical.